Elaboración y aplicación de una guía de recreación infantil que permita desarrollar la autoestima personal de los niños de 5 a 6 años de edad de la escuela Riobamba de Pilacoto de la parroquia Guaytacama en el año lectivo 2013 – 2014 - Caisa Gavilema, Lastenia Maribel (2014)
The present investigative work is related to the elaboration of a children`s amusement guide in order to improve the children`s self-esteem of the “Riobamba” school of Pilacoto, that belongs to the Guaytacama. A conceptual, critic and analytical review was taken on infantile amusement, which is based on ludic and popular games, besides methodological strategies that allow to visualize teaching using dynamic and dialectic methods according to the Critiquing Teaching without letting aside self-esteem, which is essential part so that the child has a well- established personality and he can be able to succeed in life. The teaching-learning process by means of controlled ludic and children’s games was pointed out, which allowed the shift in the behavior of children and the critiquing and reflexive responsibility….